Laparoscopic but not open surgical skills can be transferred to robot-assisted surgery: a systematic review and meta-analysis: scientific review - Schmidt, Mona Wanda; Fan, Carolyn; Köppinger, Karl F.; Schmidt, Leon P.; Brechter, Anna; Limen, Eldrige F.; Vey, Johannes; Metz, Matthes; Müller, Beat P.; Nickel, Felix; Kowalewski, Karl-Friedrich (World journal of surgery, 2024)
Background With an increase in robot-assisted surgery across all specialties, adequate training and credentialing strategies need to be identified to ensure patients safety. The meta-analysis assesses the transferability of technical surgical skills between laparoscopic surgery, open surgery, and robot-assisted surgery. Design A systematic search was conducted in Medline, Cochrane Central Register of Controlled Trials, and Web of Science. Outcomes were categorized into time, process, product, and composite outcome measures and pooled separately using Hedges'g (standardized mean difference [SMD]). Subgroup analyses were performed to assess the effect of study design, virtual reality platforms and task difficulty. Results Out of 14,120 screened studies, 30 were included in the qualitative synthesis and 26 in the quantitative synthesis. Technical surgical skill transfer was demonstrated from laparoscopic to robot-assisted surgery (composite: SMD 0.40, 95%-confidence interval [CI] [0.19; 0.62], time: SMD 0.62, CI [0.33; 0.91]) and vice versa (composite: SMD 0.66, CI [0.33; 0.99], time [basic skills]: SMD 0.36, CI [0.01; 0.72]). No skill transfer was seen from open to robot-assisted surgery with limited available data. Conclusion Technical surgical skills can be transferred from laparoscopic to robot-assisted surgery and vice versa. Robot-assisted and laparoscopic surgical skills training and credentialing should not be regarded separately, but a reasonable combination could shorten overall training times and increase efficiency. Previous experience in open surgery should not be considered as an imperative prerequisite for training in robot-assisted surgery. Recommendations for studies assessing skill transfer are proposed to increase comparability and significance of future studies. PROSPERO Registration Number PROSPERO CRD42018104507.